STRATEGI GURU IPS DALAM PENANAMAN NILAI KARAKTER SOSIAL SISWA DI KELAS IX SMPN 3 TAROGONG KIDUL - Asti Nur Oktaviani; Triani Widyanti; Hendro Sugiarto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the strategies employed by Social Studies teachers in instilling social character values among ninth-grade students at SMPN 3 Tarogong Kidul and to identify the supporting and inhibiting factors in the implementation process. The study employed a qualitative method with a descriptive approach. The theoretical framework was based on Thomas Lickona’s character education theory, which emphasizes moral knowing, moral feeling, and moral action. Data analysis was conducted using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that Social Studies teachers can instill social character values through role modeling, habituation, group discussions, and providing opportunities for students to actively participate in learning activities. Supporting factors include teacher role models, a conducive school environment, and family support. Meanwhile, inhibiting factors include the influence of social media, differences in family backgrounds, students’ low awareness of the importance of social character values, and peer group influences. Therefore, collaboration among schools, families, and communities is essential to ensure the effective and sustainable development of students’ social character values.